International financial markets : prices and policies - Levich, Richard M. (Boston, Massachusetts. : Irwin/McGraw-Hill, 1998)
The purpose of the book is to analyze the key financial markets and instruments that facilitate trade and investment activity on a global scale.
Includes bibliographical references and indexes.
osc 27/7/16
Loan
Keywords: Investments, Foreign; International finance; Securities